The Managing Director's Global Policy Agenda, Annual Meetings 2020 : Catalyzing a Resilient Recovery. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
The global economic outlook is improving, but the recovery is partial, uneven, and uncertain. Policies must restore confidence, support jobs, and boost growth. Now is the time to also build a more resilient future. We must work together to support the most vulnerable countries and people.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund Member; Policy Advice; Policy Credibility; PP; Risk Management Capability